(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study determined the effect of gender on senior secondary school students’ creativity in dataprocessing in Anambra State, Nigeria. Two research questions guided the study and two null hypotheses were tested. Quasi-experimental research design specifically, pre-test post-test non- equivalent control group design was adopted for the study. Population was 3,182 senior secondarytwo (SS2) Data Processing students in 2022/2023 academic session in Anambra State. Amulti-stagerandom sampling technique was used to select a sample size of 60 intact class SS2 students for thestudy. Rating Scale for Creativity Skills in Data Processing was used for data collection. The face andcontent validity of the instruments were established using three experts. The reliability of theinstrument was established through pilot testing method and data collected calculated usingCronbach’s alpha which yielded coefficient values of .91. Mean was used to answer the researchquestions while Analysis of Covariance (ANCOVA) was used to test the null hypotheses at 0.05 level of significance. Findings of the study revealed that there was no significant difference in the meancreativity score of male and female students taught data processing using brainstorming teachingstrategy. Furthermore, there was no significant interaction effect between the teaching methods andgender on students’ creativity in data processing. The researcher therefore, recommended that, gender differences should not be introduced in brainstorming classrooms